2012
DOI: 10.1111/j.1524-4725.2011.02234.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Treatment Modalities for Vitiligo

Abstract: Our ability to treat vitiligo may be imperfect, but through appropriate patient selection and careful application of one or more of these advanced therapies, successful treatment of vitiligo, even in patients refractory to treatment, can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 53 publications
0
51
0
Order By: Relevance
“…The recipient site is also prepared by taking multiple punch biopsies that are the same size or 0.25 to 0.5 mm smaller than those taken from the donor site. 18 Most of the authors prefer the use of similar size of punch grafts from both the sites. The grafted tissue from the donor site is then secured into the vitiliginous areas.…”
Section: Punch Graftingmentioning
confidence: 99%
See 3 more Smart Citations
“…The recipient site is also prepared by taking multiple punch biopsies that are the same size or 0.25 to 0.5 mm smaller than those taken from the donor site. 18 Most of the authors prefer the use of similar size of punch grafts from both the sites. The grafted tissue from the donor site is then secured into the vitiliginous areas.…”
Section: Punch Graftingmentioning
confidence: 99%
“…Thus it has been proposed that 1.5 mm should be the upper size limit for punch grafts on the trunk or extremities and 1 mm on the face. 18,23 Lahiri and Sengupta suggested that a resistant cobblestoning may be corrected with electrofulguration. 24 Agarwal et al(1999) used silicone gel sheet dressings for prevention of post minigraft cobblestoning.…”
Section: Disadvantagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these surgical approaches, punch grafting represents a simple and effective procedure, which involves performing multiple perforations in the recipient depigmented site using biopsy punches and transplanting similar size punches harvested from a normally pigmented donor site. [3][4][5][6] Additional treatments such as narrow band ultraviolet B (NB-UVB), psoralen plus ultraviolet A (PUVA)/khellin plus ultraviolet A (KUVA) or topical corticosteroids following the grafting can further promote the pigmentation process. These therapies aim at repigmenting the lesional skin and stimulating the melanocyte activation, proliferation and migration.…”
Section: Introductionmentioning
confidence: 99%